AKTIVITAS FISIK, PENGETAHUAN GIZI, ASUPAN ENERGI, ASUPAN SERAT DAN STATUS GIZI LEBIH PADA REMAJA - Maharani, Maharani; Desri Suryani, Darwis, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Nutrition problems in adolescents are found in many nutrients. More nutrition (overweight) is one of the epidemic problems worldwide. Objective of the study to determine the relationship of physical activity, nutritional knowledge and fiber intake with more nutritional status in adolescents in MTSN 2 Kota Bengkulu.Penelitian this is with observational research using cross sectional design. Population taken in this research is all students of class VII and VIII in MTSN 2 City of Bengkulu Year 2017. Sampling by purposive sampling technique. The results of research on average light physical activity, adequate nutritional knowledge, energy intake more than AKG and fiber intake less than AKG. There is a relationship between physical activity, knowledge, energy intake, fiber intake with more nutritional status in adolescent (p <0,05). The most dominant variables associated with more nutritional status are nutritional knowledge (p = 0,000). The importance of adding nutritional knowledge about obesity in adolescents in order to increase physical activity and fiber intake and reduce energy intake so as to achieve good nutritional status.